Wicked lovely eaudiobook - Marr, Melissa (Wicked Lovely, 2007)
A dazzling 21st-century faerie tale, Wicked Lovely is Melissa Marr's thrilling and enchanting debut novel. Aislinn is a teenage girl who possesses the seer's sight-a gift (or curse) that reveals to her the hordes of fey kind who mingle mischievously among mortals undetected. And Keenan, a powerful, radiantly stunning faerie-both terrifying and alluring-has taken a special interest in Aislinn.